UMP recognised as most active blood donation organiser - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 14 June 2022 - Universiti Malaysia Pahang (UMP) received the 2021 Most Active Organiser award in conjunction with the recent Pahang statewide World Blood Donor Day Celebration.